(3QSGdI aj JRhjL GejQ GdeDefjf GHfJgs - (3CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QHH GdYGdejf (B... (3SCdfj GdQFjS (B.. (3Yf GdSHH aj GfcGM CejQ GdeDefjf Ydj HfJg YeQ Hf GdNWGH acja jUM Pdc eY GYJbGO GdTjYI GdEeGejI aj YeQ Gfg Ydi MGd dG jLhR eYgG GfcGMgs
(3BNQgG (B:s
(3BNQgG(B: (3hcja jHjM GdYbO ef dG jLhR efGcMJg hdG YbO GdfcGM dg hEPG GHGMg HGdYbO GdhGbY GdJeJY acja HefYg eeG jbJVjg GdYbO hGdefY aj GdYbO Ghdi (B.... (3hgPg LedI eZfjI Yf PcQ ShGgG hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 278s
(3GdPQjYI, L (B5: 130s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds